Strategi Pengembangan Model Bisnis Koperasi Rumput Laut dengan Pendekatan Cooperative and Mutual Enterprise Business Model Canvas - Sianggaputra, Muhammad Danny; Asnawi, Yudha Heryawan; Indrawan, Dikky (Jurnal Maksipreneur, 2025)
This study aims to develop a seaweed cooperative business model based on the Cooperative and Mutual Enterprise Business Model Canvas (CME-BMC) to enhance the cooperative’s competitiveness and adaptive capacity in supporting small-scale farmers. The research utilizes a qualitative case study of a seaweed cooperative in West Java, integrating the CME-BMC with the VRIO, PESTEL, and SWOT frameworks through literature review, in-depth interviews, and structured questionnaires. The findings show that the current business model is aligned with cooperative principles, but it still has weaknesses that need to be strengthened for the cooperative to effectively compete and grow. The cooperative's key resources and capabilities include integrated post-harvest and processing facilities, experienced members, democratic governance, and effective management of the value chain across both upstream and downstream activities. The external environment presents both opportunities and challenges within the industry, including policy support, land allocation issues, climate risks, price fluctuations, and downstream regulations. Nine development strategies were formulated and translated into a new, more integrated and member-oriented business model. This study offers practical and theoretical contributions by demonstrating how the integration of the CME-BMC with strategic analysis can produce a more adaptive, sustainable, and competitive cooperative business model.